Forecasting of Using Electricity Consumption at ITERA (Institut Teknologi Sumatera) until 2025, to Improve Application of Renewable Energy in Lampung Province - Baqaruzi, Syamsyarief; Muhtar, Ali; Puradimaja, Deny Juanda (Universitas Diponegoro, 2021)
Institut Teknologi Sumatera (ITERA) is a new campus located in Lampung province- Indonesia. It is almost 6 years old, within large data on the total population human activity in this 275-hectare campus around 9500 persons, so that necessary to forecasting energy demand in the future, ITERA can project programs that are in line with the Indonesian government, specifically increasing using of renewable energy. which the government has a national energy policy in 2025 of 23%. Mostly in Lampung province, the electricity produced is still dominated by fossil energy (e.g., coal, diesel, etc), therefore as a campus with a technological background, ITERA must be able to bring a paradigm shift to be used from electricity consumption in the surrounding areas. The results of this study will project electricity usage in ITERA over the next 5 year, where electricity usage in ITERA 2019 is 2.472 GWh or 6,775 KWh/day, expected with a development strategy to implementing the efficiency of green energy, so that can meet the challenges of reducing CO2 emissions and energy-saving behavior, also keep sustainable impact for Indonesia.